Pesatnya Perkembangan AI (Artificial Intelligence) : Peluang atau Bumerang Dalam Masa Depan Pendidikan - Ardiawan, I Ketut Ngurah; Pratiwi, Komang Dinda Septina; Jessika, Kadek Reka (Adi Widya: Jurnal Pendidikan Dasar, 2025)
Artificial intelligence (AI) technology has advanced rapidly, providing intelligent and efficient solutions to various societal challenges across different aspects of life, including education. AI has introduced numerous innovative breakthroughs in the education sector, such as text-to-video technology, AI-generated questions and quizzes, and AI-assisted foreign language learning. These advancements have made teaching and learning processes significantly easier for both educators and students. The types of AI technologies used in education include ChatGPT, voice assistants, smart content, presentation translators, and virtual mentors. The use of AI technology creates both opportunities and challenges. The opportunities include improving feedback and evaluation in education, enhancing access to educational resources for students, supporting independent learning, and fostering better understanding among learners. However, these opportunities come with challenges such as dependence on AI technology, ethical and legal violations due to AI plagiarism, and technological limitations that may pose risks to the future of education. Therefore, the roles of governments, teachers, and parents are crucial in preparing students to use AI technology wisely.